Emphasizing reflective processes in scientific inquiry and its impact on preservice science teachers’ critical thinking skills - Saiful Prayogi; Ni Nyoman Sri Putu Verawati; Muhammad Roil Bilad; Taufik Samsuri; Hunaepi; Muhammad Asy'ari; Muhammad Yusril Yusup; Irham Azmi; Nevi Ernita (Social Sciences and Humanities Open)
Adequate pedagogical infrastructure is necessary to continue honing critical thinking skills in preservice science teachers (PSTs), given their central role in training future science students. In the classroom routine of science teaching, inquiry is embedded as a process of teaching how to think, but it is not robust enough to develop the critical thinking. This study investigate examines the reflective process in scientific inquiry and evaluate its impact on the critical thinking skills of PSTs. The study employed a mixed methods approach (quantitative and qualitative) by grouping participants into experimental and control. Quantitative data demonstrated that reflective process significantly enhanced the critical thinking skill performance, much better than the traditional teaching used as the control. The qualitative analysis based on interviews with the lecturers revealed that the reflective processes was highly effective in aligning with students’ situational interests in various academic environments. It captured their attention, making the learning process enjoyable and engaging, and was considered important and valuable by the PSTs. It ultimately enhanced the critical thinking skills and a deepened the understanding of the subject matter. These findings establish the importance of reflective practices in scientific inquiry, proving valuable in optimizing teaching and learning processes and fostering professional growth.